Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 168188 by cortano1 last updated on 05/Apr/22

     ∫ ((1−sin 2x)/((1+sin 2x)^2 )) dx =?

1sin2x(1+sin2x)2dx=?

Commented by Florian last updated on 09/Apr/22

  ?=(1/(2(√2)))arctan((√2) tan(2x))+(1/(4(√2)))(ln∣(1/( (√2)))cos(2x)+1∣ ln∣(1/( (√2)))cos(2x)−1∣)+c, c∈R

?=122arctan(2tan(2x))+142(ln12cos(2x)+1ln12cos(2x)1)+c,cR

Answered by peter frank last updated on 05/Apr/22

1−sin 2x=(cos x−sin x)^2   (1+sin 2x)^2 =(cos x+sin x)^4   ∫(((cos x−sin x)^2 )/((cos x+sin x)^4 ))dx  ∫(((1−tan  x)^2 )/((1+tan  x)^4 ))dx.sec^2 x  t=tan x       dx=(1/(sec^2 x))dt  ∫(((1−t)^2 )/((1+t)^4 ))dt  .......

1sin2x=(cosxsinx)2(1+sin2x)2=(cosx+sinx)4(cosxsinx)2(cosx+sinx)4dx(1tanx)2(1+tanx)4dx.sec2xt=tanxdx=1sec2xdt(1t)2(1+t)4dt.......

Answered by Mathspace last updated on 05/Apr/22

I=_(2x=t)  (1/2)  ∫  ((1−sint)/((1+sint)^2 ))dt ⇒  f(λ)=∫  ((1−sint)/(λ+sint))dt ⇒  f^′ (λ)=−∫ ((1−sint)/((λ+sint)^2 ))dt ⇒  ∫ ((1−sint)/((1+sint)^2 ))=−f^′ (1)  f(λ)=_(tan((t/2))=x)    ∫  ((1−((2x)/(1+x^2 )))/(λ+((2x)/(1+x^2 ))))((2dx)/(1+x^2 ))  =2∫  ((1+x^2 −2x)/((1+x^2 ){λ+λx^2 +2x}))dx  we decompose F(x)=((x^2 −2x+1)/((x^2 +1)(λx^2 +2x+λ)))  F(x)=((ax+b)/(x^2 +1))+((cx+d)/(λx^2 +2x+λ))  ⇒(ax+b)(λx^2 +2x+λ)+(cx+d)(x^2 +1)  =x^2 −2x+1 ⇒  λax^3 +2ax^2 +λax +λbx^2 +2bx+λb  cx^3 +cx+dx^2 +d=x^2 −2x+1 ⇒  (λa+c)x^3 +(2a+λb+d)x^2 +(λa+2b+c)x  +λb+d=x^2 −2x+1 ⇒  λa+c=o ,2a+λb+d=1 ,λa+2b+c=−2  λb+d=1....be continued....

I=2x=t121sint(1+sint)2dtf(λ)=1sintλ+sintdtf(λ)=1sint(λ+sint)2dt1sint(1+sint)2=f(1)f(λ)=tan(t2)=x12x1+x2λ+2x1+x22dx1+x2=21+x22x(1+x2){λ+λx2+2x}dxwedecomposeF(x)=x22x+1(x2+1)(λx2+2x+λ)F(x)=ax+bx2+1+cx+dλx2+2x+λ(ax+b)(λx2+2x+λ)+(cx+d)(x2+1)=x22x+1λax3+2ax2+λax+λbx2+2bx+λbcx3+cx+dx2+d=x22x+1(λa+c)x3+(2a+λb+d)x2+(λa+2b+c)x+λb+d=x22x+1λa+c=o,2a+λb+d=1,λa+2b+c=2λb+d=1....becontinued....

Answered by MJS_new last updated on 06/Apr/22

∫((1−sin 2x)/((1+sin 2x)^2 ))dx=∫((2/((1+sin 2x)^2 ))−(1/(1+sin 2x)))dx=       [t=tan x → dx=(dt/(t^2 +1))]  =∫(((2(t^2 +1))/((t+1)^4 ))−(1/((t+1)^2 )))dt=  =∫((4/((t+1)^4 ))−(4/((t+1)^3 ))+(1/((t+1)^2 )))dt=  =−(4/(3(t+1)^3 ))+(2/((t+1)^2 ))−(1/(t+1))=  =−((3t^2 +1)/(3(t+1)^3 ))=  =−((1+3tan^2  x)/(3(1+tan x)^3 ))+C  [=−((cos^3  2x)/(6(1+sin 2x)^3 ))+C]

1sin2x(1+sin2x)2dx=(2(1+sin2x)211+sin2x)dx=[t=tanxdx=dtt2+1]=(2(t2+1)(t+1)41(t+1)2)dt==(4(t+1)44(t+1)3+1(t+1)2)dt==43(t+1)3+2(t+1)21t+1==3t2+13(t+1)3==1+3tan2x3(1+tanx)3+C[=cos32x6(1+sin2x)3+C]

Commented by peter frank last updated on 06/Apr/22

thank you

thankyou

Answered by greogoury55 last updated on 06/Apr/22

 T=∫ ((1−sin 2x)/((1+sin 2x)^2 )) dx    [ tan x=t → { ((dx=(dt/(1+t^2 )))),((sin 2x=((2tan x)/(1+tan^2 x))=((2t)/(1+t^2 )))) :}]   T=∫ ((1+t^2 −2t)/((1+t^2 +2t)^2 )) dt    =∫ (((t−1)^2 )/((t+1)^4 )) dt = ∫ ((1/((t+1)^2 )) −(4/((t+1)^3 )) +(4/((t+1)^4 )))dt    = −(1/(t+1)) +(2/((t+1)^2 ))−(4/(3(t+1)^3 )) + c    = −(1/(1+tan x)) +(2/((1+tan x)^2 )) −(4/((1+tan x)^3 )) + c

T=1sin2x(1+sin2x)2dx[tanx=t{dx=dt1+t2sin2x=2tanx1+tan2x=2t1+t2]T=1+t22t(1+t2+2t)2dt=(t1)2(t+1)4dt=(1(t+1)24(t+1)3+4(t+1)4)dt=1t+1+2(t+1)243(t+1)3+c=11+tanx+2(1+tanx)24(1+tanx)3+c

Commented by peter frank last updated on 07/Apr/22

thank you

thankyou

Terms of Service

Privacy Policy

Contact: info@tinkutara.com